CASE STUDY OF MIDWIFERY CARE FOR COMPLETE ABORTION AT 10 WEEKS GESTATION - situmeang, yen; Rumondang Sitorus; Saydina Ginting; Jesyka Darma Kasi; Angel (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Early pregnancy loss remains a significant contributor to maternal morbidity and has the potential to cause complications, including excessive bleeding, infection, anemia, and psychological problems when appropriate management is not provided. Therefore, comprehensive and prompt midwifery care is essential to promote maternal recovery and minimize the risk of further complications (Shimels et al. 2023) Objectives: This study aimed to describe the implementation of comprehensive midwifery care in Mrs. I, a 24-year-old G1P0A1 woman with a gestational age of 10 weeks who experienced complete abortion at Pratama Vina Clinic, North Sumatra. Methods: A descriptive case study design was used with Varney’s seven-step midwifery management approach. Data were obtained through interviews, physical examinations, observations, and documentation. The care provided was documented using the SOAP format. Results: The patient presented with complaints of lower abdominal cramps accompanied by vaginal bleeding and expulsion of tissue. Examination findings showed blood pressure of 110/80 mmHg, pulse rate of 100 beats/minute, respiratory rate of 20 breaths/minute, body temperature of 36.5°C, and ultrasonography findings indicating an empty uterine cavity. Midwifery management included monitoring vital signs, providing health education, recommending adequate rest and genital hygiene, administering iron tablets, folic acid, and vitamin C, providing counseling regarding temporary pregnancy postponement, offering psychological support, and recommending follow-up visits. Evaluation results showed that the patient and her husband understood the information provided, anxiety decreased, and the patient’s physical condition improved without complications. Conclusions: The implementation of comprehensive midwifery care using Varney’s seven-step approach was carried out effectively and contributed to improving the patient’s condition, accelerating recovery, and preventing complications following pregnancy loss.